2022
DOI: 10.1038/s41588-022-01232-7
|View full text |Cite
|
Sign up to set email alerts
|

Cohesin and CTCF control the dynamics of chromosome folding

Abstract: In mammals, interactions between sequences within topologically associating domains enable control of gene expression across large genomic distances. Yet it is unknown how frequently such contacts occur, how long they last and how they depend on the dynamics of chromosome folding and loop extrusion activity of cohesin. By imaging chromosomal locations at high spatial and temporal resolution in living cells, we show that interactions within topologically associating domains are transient and occur frequently du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
93
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(123 citation statements)
references
References 63 publications
(95 reference statements)
28
93
2
Order By: Relevance
“…We observe that cohesin and condensin, both harboring ATPase activity, constrain chromatin mobility in vivo; a similar observation was recently reported for the effect of cohesin depletion in mouse ES cells (Mach et al, 2022). These data further mirror prior observations in budding yeast for cohesin depletion (Cheblal et al, 2020), although this effect was ascribed primarily to an effect on sister chromatid cohesion rather than loop extrusion.…”
Section: Loops As Constraints To Chromatin Mobilitysupporting
confidence: 90%
See 1 more Smart Citation
“…We observe that cohesin and condensin, both harboring ATPase activity, constrain chromatin mobility in vivo; a similar observation was recently reported for the effect of cohesin depletion in mouse ES cells (Mach et al, 2022). These data further mirror prior observations in budding yeast for cohesin depletion (Cheblal et al, 2020), although this effect was ascribed primarily to an effect on sister chromatid cohesion rather than loop extrusion.…”
Section: Loops As Constraints To Chromatin Mobilitysupporting
confidence: 90%
“…1b). Taking a different simulation approach for examining the effect of loop extrusion that also accounts for volume exclusion, Mach et al likewise found recently that it is the act of loop extrusion rather than the influence of specific boundaries (or barriers) that impacts polymer dynamics, although they did not observe changes to the anomalous exponent, α (Mach et al, 2022). Taken together, these observations highlight that chromatin dynamics is dominated by the polymer nature of the chromatin and not by the local genomic conformation on the seconds time scale.…”
Section: Discussionmentioning
confidence: 99%
“…In the hierarchical chromatin organization described above, the loop domain is assumed to be held by cohesin (31,(33)(34)(35). However, how the domain looks in a living cell remains unclear (i.e., do loops form a cluster of nucleosomes or extend).…”
Section: Introductionmentioning
confidence: 99%
“…In the studied locus, the processivity, that is the extrusion velocity divided by the extruder dissociation rate, is 700 kb, while 10 is the number of extruding factors [ 65 ]. We point out, however, that fresh data from live-cell imaging technologies could help in a more precise and quantitative calibration of the LE dynamic parameters, as also discussed in recent studies [ 41 , 42 ].…”
Section: Resultsmentioning
confidence: 74%
“…Those studies, by allowing a direct visualization of chromatin conformations in individual nuclei, highlighted, for example, the abundance of TAD-like domains in single cells and their broad cell-to-cell structural heterogeneity, thus adding important constraints on chromosome folding beyond population-averaged contacts [ 13 , 40 ]. Additionally, recent live-cell imaging reports are enabling to track in time the dynamic of specific chromatin loci and the transient behavior of DNA functional interactions at the single-molecule level, unveiling the fourth dimension of genome topologies with a resolution of very few seconds [ 41 , 42 ].…”
Section: Introductionmentioning
confidence: 99%